Pengaruh Pelatihan dan Kompetensi Terhadap Kinerja Karyawan di Rumah Sakit Dewi Sri Karawang - Mutia Wulan Maelani; Sari Marliani; July Yuliawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study's objective was to investigate effects of competency and instruction in worker accomplishment, particularly at Dewi Sri Karawang Hospital. Using a sample of 79 respondents, quantitative approaches were used to conduct this study. To determine training, competency, and its effect on performance, a The data was collected using the survey approach . After that, the survey data were examined using the multiple linear analysis approach, with employee performance (Y) serving as the dependent variable and training (X1) and competency (X2) serving as the independent variables. According to the study's findings, competency and training significantly affect how well employees work at Dewi Sri Karawang Hospital. Competency, however, has a stronger effect than training, since training scored 3.181 with an average of 318 on good criteria; Competency obtained a score of 3.352 with an average of 325 on good criteria; and performance obtained a score of 3.175 with an average of 317 on good criteria. This research also has implications for how Dewi Sri Karawang Hospital must pay more attention to the level of training and competency to improve and enhance the quality of performance, especially in terms of community services.